A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China - Wu, San-An; Wang, Xubo (Zootaxa, 2019)
The fifteen Ceroplastes species recorded from China are discussed in relation to the origin, distribution, host-plants, biology and remarks. Of these, one new species, Ceroplastes planus Wu & Wang, sp. nov., is described and illustrated; and C. magnificus (Green) is recorded from China for the first time. A key to species of Ceroplastes now known from China is provided.